Policing’s New Vulnerability Re-Envisioning Local Accountability in an Era of Global Outrage - Goldsmith, Andrew John (The British journal of criminology, 2022)
In this paper, we argue that globally networked activism such as that triggered by the murder of George Floyd has dramatically amplified, and consequently rendered processes of police reform and accountability more vulnerable to exogenous influences. Recently witnessed activism in this sphere derives much of its significance from the ability to leverage the latest audio-visual technologies and social media platforms. The Black Lives Matter protests demonstrate how these technologies and platforms make flashpoint images of violent policing visible to diverse, global audiences in an extraordinary manner. Using the examples of Australia and the United Kingdom, we argue that these viral images have the capacity to ‘collapse contexts’ and radically disrupt policing in the places to which they migrate. The complicated impact of migrating flashpoint images of violent policing from ‘over there’ to ‘over here’ necessitates urgent analysis and debate.